Elements of a European ports policy - Rudolf Regul (Intereconomics, 1973)
Shipping and ports are like Siamese twins: neither can live without the other. The trouble is that due to rapid technical progress in shipbuilding it has become difficult to provide the shipping industry with both in the right proportion and at the same time.
Keywords: 330; Shipping